Long-term paired associative stimulation can restore voluntary control over paralyzed muscles in incomplete chronic spinal cord injury patients - Shulga, Anastasia (Spinal Cord Ser Cases, 2016)
Emerging therapeutic strategies for spinal cord injury aim at sparing or restoring at least part of the corticospinal tract at the acute stage. Hence, approaches that strengthen the weak connections that are spared or restored are crucial. Transient plastic changes in the human corticospinal tract can be induced through paired associative stimulation, a noninvasive technique in which transcranial magnetic brain stimulation is synchronized with electrical peripheral nerve stimulation. A single paired associative stimulation session can induce transient plasticity in spinal cord injury patients. It is not known whether paired associative stimulation can strengthen neuronal connections persistently and have therapeutic effects that are clinically relevant. We recruited two patients with motor-incomplete chronic (one para- and one tetraplegic) spinal cord injuries. The patients received paired associative stimulation for 20–24 weeks. The paraplegic patient, previously paralyzed below the knee level, regained plantarflexion and dorsiflexion of the ankles of both legs. The tetraplegic patient regained grasping ability. The newly acquired voluntary movements could be performed by the patients in the absence of stimulation and for at least 1 month after the last stimulation session. In this unblinded proof-of-principle demonstration in two subjects, long-term paired associative stimulation induced persistent and clinically relevant strengthening of neural connections and restored voluntary movement in previously paralyzed muscles. Further study is needed to confirm whether long-term paired associative stimulation can be used in rehabilitation after spinal cord injury by itself and, possibly, in combination with other therapeutic strategies.